An insider looking in or an outsider wannabee? Studying vulnerable hard-to-reach populations in the field of victimology – the example of the Roma communities in Sweden - Wallengren, Simon (International review of victimology, 2021)
This article reviews methodological barriers to victimological research on vulnerable hard-to-reach populations and presents a reflexive discussion of insider and outsider positions in a study researching Roma communities’ victimization in Sweden. As a Roma (Traveler/resande) academic, I found that some aspects of my identity were linked to an insider position, while other aspects of my identity were often perceived by study participants as outsider attributes. Within the framework of critical reflexivity, this article considers the impact of my insider/outsider position at each stage of the research process. The article rearticulates the importance of researcher reflexivity, mainly when both researchers and participants exhibit multiculturality, which has become more common in the globalized world.